Friday

July 25, 2014

July 25, 2014

Posted by **christina** on Saturday, September 14, 2013 at 12:04am.

x= 1-t^2

y=t-2

-2 _<t _<2

known: -4 <(or=) y <(or =) 0

I got y= sq(x-1)+2

- MATH ASAP -
**Graham**, Saturday, September 14, 2013 at 5:12amClose.

Rearrange x = 1 - t^2:

t = ±√(1-x)

Substitute into: y = t - 2

y = -2 ± √(1-x)

--Alternatively--

Rearrange : y = t - 2

t = y + 2

Substitute into x = 1 - t^2

x = 1 - (y+2)^2

Thus:

x = -3 - 4y - y^2

**Related Questions**

calculus - I don't quite understand Cartesian equations. I am told to Eliminate ...

Curves defined by parameteric equations - Consider the following. x = e^t - 12 y...

calculus - (a) Modifying the parametric equations of a unit circle, find ...

Calculus - I'm extremely confused on what to do in part a of this question. ...

Math - This question makes reference to an orthonormal basis (i,j), and an ...

Math - Eliminate the parameter and write the corresponding rectangular equation ...

Math - Eliminate the parameter and write the corresponding rectangular equation ...

Calc - Find a cartesian equation for the curve described by the given polar ...

Calc AB - eliminate the parameter and write a rectangular equation for x=(t^2)+3...

Math - Eliminate the parameter in the pair of parametric equations to find the ...